PENGARUH PERGANTIAN AUDITOR, JENIS INDUSTRI, ANAK PERUSAHAAN (SUBSIDIARY), KEPEMILIKAN PUBLIK DAN LEVERAGE TERHADAP ADUIT DELAY PADA PERUSAHAAN PERDAGANGAN DAN INVESTASI YANG TERDAFTAR DI BEI PADA TAHUN 2016 – 2019 - Tandi, Alex Sander (Akuntansi Prima, 2020)
The research is intended to analyze and examine whether changes in auditors, types of industries, subsidiary, public ownership, and leverage affect audit delay on the commerce and investments listed in the Indonesian stock exchange during 2016-2019. This research using analysis method and through the causal relationship of as many as 79 sample results are selected, where 316 observations are passed conditional. Sample retrieval technique obtained from an impressive sampling. Testing of the hypotheses and data analysis with regression methods obtained from SPSS 20 partial and simultaneously indicates that changes in auditors, types of industries, subsidiary companies, public ownership and leverage did not affect, and little effect on auditory delays in trading and investment from 2016 to 2019 recorded in the Indonesian stock exchange. Key words: change of auditors, types of industries, subsidiaries, public ownership,leverage, audit delay.